Camera systems and their user recognition reliability when entering an agri-food complex - Jaroslav Mrázek; Jakub Vošáhlík; Eva Olmrová; Martin Pexa; Zdeněk Aleš; Jakub Čedík (Research in Agricultural Engineering)
This study evaluates the efficiency of various facial recognition camera systems used to control access in agri-food production environments, focusing on their ability to identify individuals based on biometric facial traits. It is also important to prevent the movement of unwanted persons into the production premises in the agri-food complex. The main goal was to assess how these factors influence the recognition performance and to determine the most reliable system for preventing unauthorised entry. The results show notable performance disparities between the devices tested. It can be concluded in this research that there are statistically significant differences between the maternal, professional and semi-professional systems. The device that is most suited is the HIKVISION iDS-2CD8426G0/F-I, achieving the best average performance score. This is based on usual recognition times. These tests indicate that the HIKVISION DS-2DE7232IW-AE(S5), which obtained an average rating of 2.216789, is the second-best acceptable device. With a score of 2.842113, HIKVISION DS-2CD2H45FWD-IZS (2.8-12 mm) (B) received, without a doubt, the lowest ranking. Given the outcomes, systems with superior recognition capabilities like the iDS-2CD8426G0/F-I are best to use for critical access control applications and to also minimise the use of facial coverings in sensitive areas to ensure reliable identification and higher levels of security of agri-food complexes.